THE CRITICS AND POLITICAL EDUCATION OF THE FICTIONAL PRESIDENTIAL CANDIDATES, NURHADI & ALDO (IN THE PERSPECTIVE OF CRITICAL DISCOURSE AND SEMANTICS) - Millatuz Zakiyah; Prima Zulvarina; Destriana Saraswati (Hasta Wiyata, 2020)
The emergence of a fictitious presidential candidate, Nurhadi and Aldo, in the internet, potentially becomes the breaker of society’s polarization, as well as a media to criticize the government and some political elites. This research is talking about 1) the aims behind the emergence of Nurhadi & Aldo as alternative candidates in the presidential election, and 2) the strategies of Nurhadi & Aldo to get those aims through the perspective of semantics and critical hypothesis analysis. The data of this qualitative study are collected from the instagram account of @nurhadi_aldo and some of its derivative accounts. The result of the study shows that the purposes or aims behind the emergence of Nurhadi & Aldo as fictitious presidential candidates are 1) the medium of critics towards the government and some political elites, 2) the mode of political education through politics of leisure, and 3) the suggestion for the society to put national unity first, in the middle of societal polarizations. To get those aims, the accounts are using strategies such as 1) the usage of figures of speech, such as comparison, satire, contradiction, and affirmation, 2) the usage of polysemy , 3) the usage of sylogism, and 4) the usage of abbreviations.